Studi Keperilakuan Wajib Pajak Orang Pribadi Usahawan Terhadap Kepatuhan Perpajakan - Sifera Patricia Maithy; Sutrisno Sutrisno; Bambang Hariadi (Jurnal Akuntansi dan Pajak, 2019)
This study aims to examine the taxpayer compliance behavior of individuals on all tax obligations. Factors affecting taxpayer compliance behavior of individual taxpayers in this study are attitudes toward taxes, subjective norms, control of perceptive behavior, tax knowledge, and intention to obey. This research is the development of tax compliance model from previous research. The sample of this research is 160 individual taxpayer individual entrepreneur category registered in KPP Pratama Palangka Raya. Data collection was done by survey method. Data is processed using SmartPLS. The results of this study obtained empirical evidence that attitudes on taxes, subjective norms, perceptual behavior control, tax knowledge, and intention to obediently affect taxpayer compliance personal taxpayer. This research also supports the theory of planned behavior and social learning theory.